Pulmonary Pathology in Connective Tissue Disease - Urisman, Anatoly; Jones, Kirk D. (Seminars in Respiratory and Critical Care Medicine, 2014)
A significant proportion of patients with autoimmune connective tissue disease (CTD) show lung involvement that results in clinical interstitial lung disease (ILD). Surgical lung biopsy is helpful for diagnosis of CTD-ILD in many cases. In this review, we discuss the histologic manifestations of different types of CTD-ILD, focusing on patterns of disease and their differential diagnoses. Acquired autoimmune connective tissue diseases will be covered in this review, while lung involvement in vasculitides, heritable connective tissue disorders, and drug-induced CTD-like conditions will not be discussed.
Keywords: autoimmune connective tissue disease; collagen vascular disease; lung pathology; pulmonary pathology; lung biopsy